Arthroscopically assisted reduction of ankle syndesmotic injuries associated with malleolar fractures: Our experience - Liuni, Federico; Pogliacomi, Francesco; Battaglia, Salvatore; Ponzi, Luna; Berni, Luca; Calderazzi, Filippo; Cepparulo, Riccardo (Acta Biomedica Atenei Parmensis, 2026)
Background and aim of the work: Malleolar fractures are associated with syndesmotic lesions in up to 40% of cases. Accurate reduction and stabilization of the syndesmosis is crucial to prevent chronic instability, persistent pain and post-traumatic osteoarthritis. Ankle arthroscopy allows direct three-dimensional visualization of the distal tibiofibular joint and might improve the accuracy of reduction. The aim of this study was to evaluate the effectiveness of arthroscopically assisted reduction and fixation in ankle fractures with syndesmosis disruption. Research design and Methods: Prospective monocentric case–control study including 48 patients with AO/OTA 44B–44C malleolar fractures associated with syndesmotic injury. Group A (n=24) underwent arthroscopically assisted reduction and fixation; Group B (n=24) received conventional reduction and fixation. At a mean follow-up of 30 months, clinical outcomes (AOFAS, OMAS, VAS), specific syndesmotic tests (Squeeze test, External Rotation Stress Test, Cotton test, anterior tibiofibular tenderness) and CT-based measurements (tibio-fibular clear space, fibular rotation angle) were assessed. Non-parametric statistics were applied. Results: Significantly higher functional scores were recorded in Group A (AOFAS 91.7±9.9 vs 81.8±14.2, p=0.016; OMAS 86.0±14.2 vs 70.6±20.7, p=0.0019) and a significantly lower difference in fibular rotation angle compared with the contralateral ankle (2.71°±3.44 vs 7.41°±4.80, p<0.001). The Squeeze test was positive in 12.5% of Group A vs 45.8% of Group B (p=0.029). Conclusions: Arthroscopically assisted surgery is associated with more accurate anatomical and rotational reduction and significantly better functional outcomes at mid-term follow-up. Arthroscopy represents a valuable adjunct in the surgical management of ankle fractures associated with syndesmotic injury.